Waltzing Binaries: Probing the Line-of-sight Acceleration of Merging Compact Objects with Gravitational Waves - Aditya Vijaykumar; Avinash Tiwari; Shasvath J. Kapadia; K. G. Arun; Parameswaran Ajith (The Astrophysical Journal, 2023)
The line-of-sight acceleration of a compact binary coalescence (CBC) event would modulate the shape of the gravitational waves (GWs) it produces with respect to the corresponding nonaccelerated CBC. Such modulations could be indicative of its astrophysical environment. We investigate the prospects of detecting this acceleration in future observing runs of the LIGO-Virgo-KAGRA network, as well as in next-generation (XG) detectors and the proposed DECIGO. We place the first observational constraints on this acceleration for putative binary neutron star mergers GW170817 and GW190425. We find no evidence of line-of-sight acceleration in these events at 90% confidence. Prospective constraints for the fifth observing run of the LIGO at A+ sensitivity suggest that accelerations for typical binary neutron stars (BNSs) could be constrained with a precision of a / c ∼ 10 ^−7 [s ^−1 ], assuming a signal-to-noise ratio of 10. These improve to a / c ∼ 10 ^−9 [s ^−1 ] in XG detectors, and a / c ∼ 10 ^−16 [s ^−1 ] in DECIGO. We also interpret these constraints in the context of mergers around supermassive black holes.